Study on the causes of weathering steel corrosion for railway freight cars with a load capacity of 70 tons - Wei Du; Yi Wu; Zhongyu Yi; Ruohan Xiang; Yishuo Liu (Railway Sciences, 2025)
Purpose – Weathering steel has excellent resistance to atmospheric corrosion, but still faces complex environmental corrosion problems during long-term operation. This paper mainly studies the corrosion problem of weather resistant steel materials for railway freight car bodies with a load capacity of 70 tons. Design/methodology/approach – The paper analyzes the corrosion characteristics of weather resistant steel materials for truck bodies through macroscopic and microscopic methods including metallographic microscopy, scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction. Electrochemical analysis shows that the rust layer on the surface of weathering steel changes the surface state of the material, and also proves that weathering steel used in trucks undergoes electrochemical corrosion under atmospheric corrosion. At the same time, ion chromatography technology is used to study the corrosive ions mainly present in the residual liquid and foam solution inside the vehicle body. Findings – The corrosion of truck body materials is mainly electrochemical corrosion, and the corrosion of door materials is more obvious than that of other parts. The corrosion products are mainly Fe oxides and hydroxides. There are high concentrations of Cl – and SO42– ions in the residual liquid and foam solution at the bottom of the freight car, which are the main factors causing corrosion of the railway freight car body. Originality/value – The foam adhesive around the door panel is in a moist state for a long time, and corrosive ions will accelerate the electrochemical corrosion of the weather resistant steel material of the door panel. Therefore, the corrosion of the cargo door panel is more severe than other components.